Analisis Penerapan Sistem Manajemen Persediaan Bahan Baku Pada PT.Inkomas Lestari Untuk Menekan Inventory Cost Dengan Menggunakan Metode Economic Order Quantity (EOQ) - Ira Valentina Silalahi (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
This Research was conducted with the aim of reducing inventory costs by calculating the safety stock needed by companies using the Economic Order Quantity (EOQ) method. Based on the calculation results, it is known that PT. Inkomas Lestari with the EOQ method obtained a total inventory costs of Rp.1.888.637.963 which is lower than the company using conventional methods which have to pay a fee of Rp. 2.112.320.822, then the difference in total inventory cost is Rp. 223.682.857. This means that the Economic Order Quantity (EOQ) method can be considered more efficient compared to the conventional method currently being applied by the company